2022
DOI: 10.34172/jhp.2022.64
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of erythrocyte viability, antioxidant capacity and antiplasmodial activity induced by alkaloid extract of Phyllanthus amarus

Abstract: Introduction: The production of large amounts of reactive oxygen species in severe malarial infection is due to parasite invasion to erythrocytes. Malaria resistance to medication has left malaria-endemic countries with no alternate source of medications but traditional medicine. One of such plants utilized by traditional healers is Phyllanthus amarus. Therefore, this study aims at ascertaining the antiplasmodial and cytotoxic activities of P. amarus and its specific actions on retaining erythrocyte viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…All phytochemicals of P. amarus are, therefore, non-toxic with LD50 >5000 mg/kg. This is also consistent with other reports from other researchers who documented the non toxicity of extracts of P. amarus in both in vivo and in vitro systems 8,26 . There was no significant (p>0.05) change in white blood cells (WBC) when comparing negative control with positive control group (Table 1).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…All phytochemicals of P. amarus are, therefore, non-toxic with LD50 >5000 mg/kg. This is also consistent with other reports from other researchers who documented the non toxicity of extracts of P. amarus in both in vivo and in vitro systems 8,26 . There was no significant (p>0.05) change in white blood cells (WBC) when comparing negative control with positive control group (Table 1).…”
Section: Resultssupporting
confidence: 93%
“…However, suppression by the highest dose (500 mg/kg) of the alkaloid phytochemical was notable and showed no significant difference when compared with the activity of the standard drug in blood (p>0.05). The antiplasmodial activity of Phyllanthus amarus, the plant in this study, has been reported several times by previous studies 8,14,26 . Our study further confirms this activity and suggests that the antimalarial activity of the extracts resides essentially in the activity of the alkaloids.…”
Section: Resultssupporting
confidence: 75%
“…Different parts of the plant have been reported for specific properties, and one of these properties is the antimalarial activity. Antimalarial activity of this plant have been reported in both in vivo and in vitro systems [17,18,22,23]. This antimalarial activity can be attributed to the vast array of nutrients and active biochemical compounds present in the plant [15,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Dried powdered root of Phyllanthus amarus (about 100g) was extracted with ethanol in soxhlet apparatus for 72 h. Mixture was filtered and concentrated under vacuum. The concentrated filtrate was suspended in distilled water to obtain ethanol extract [17].…”
Section: Preparation Of Ethanol Root Extractmentioning
confidence: 99%